Systematic review of unintentional injury prevention economic evaluations 2010–2019 and comparison to 1998–2009 - Mahalingam, Mallika; Peterson, Cora; Bergen, Gwen (Accident analysis and prevention, 2020)
•Two decades of unintentional injury prevention economic evaluations are summarized.•Falls and motor vehicle traffic injuries were the most common study subjects.•Only half of recent economic evaluations reported on key methods elements.•Standardized and complete reporting can improve comparisons across studies. Health economic evaluation studies (e.g., cost-effectiveness analysis) can provide insight into which injury prevention interventions maximize available resources to improve health outcomes. A previous systematic review summarized 48 unintentional injury prevention economic evaluations published during 1998–2009, providing a valuable overview of that evidence for researchers and decisionmakers. The aim of this study was to summarize the content and quality of recent (2010–2019) economic evaluations of unintentional injury prevention interventions and compare to the previous publication period (1998–2009). Peer-reviewed English-language journal articles describing public health unintentional injury prevention economic evaluations published January 1, 2010 to December 31, 2019 were identified using index terms in multiple databases. Injury causes, interventions, study methods, and results were summarized. Reporting on key methods elements (e.g., economic perspective, time horizon, discounting, currency year, etc.) was assessed. Reporting quality was compared between the recent and previous publication periods. Sixty-eight recent economic evaluation studies were assessed. Consistent with the systematic review on this topic for the previous publication period, falls and motor vehicle traffic injury prevention were the most common study subjects. Just half of studies from the recent publication period reported all key methods elements, although this represents an improvement compared to the previous publication period (25 %). Most economic evaluations of unintentional injury prevention interventions address just two injury causes. Better adherence to health economic evaluation reporting standards may enhance comparability across studies and increase the likelihood that this type of evidence is included in decision-making related to unintentional injury prevention.